Building a K3 Culture in Realizing Zero Accident & Zero Environmental Complaint - Yulita Maria; Hwihanus Hwihanus; Muhammad Bayu; Darmono Darmono (Cita konsultindo, 2023)
PT PLN (Persero) is one of the State-Owned Enterprises engaged in the Electricity sector. Work in the electricity sector is a high-risk job, if there is negligence in its management it can result in enormous losses for the company. Moreover, if it causes casualties, it will cause a human tragedy for the families left behind and have a negative impact on the company's performance and image. As stipulated in Law No. 30 of 2009 Article 44 paragraphs 1 and 2 that every electricity business must comply with electricity safety provisions, which aim to create conditions that are reliable and safe for installations, safe from harm to humans and other living things and eco-friendly. Concern for the safety of the life of the workforce encourages the company to build an K3 culture to realize zero accidents and zero environmental excellence so that it has an impact on increasing system reliability and quality of customer service. Habits in cultivating a K3 culture start from oneself, namely starting from the heart, thoughts, and actions and starting from the leadership to all workers, both employees and work partners. To realize the habit of implementing K3 culture (Occupational Safety and Health), PT PLN (Persero) Berau carries out activities including: Establishing K3 Policy, Occupational Safety and Health Planning, K3 Plan Implementation, K3 Performance Monitoring and Evaluation, K3 Performance Review and Improvement . In its implementation, this activity focuses on 3 main elements, namely: Increasing HR Risk Awareness and HSE competence (Occupational Health and Environmental Safety), Implementation of K3 Management Systems, K3L Infrastructure Improvement.